Inhalable drug-loaded nanoparticles as well as preparation method and application thereof
Nanoparticles prepared by ionic cross-linking method use self-assembly loading of nidanib using cationic polysaccharides and anionic polymers to solve the problems of low bioavailability and low encapsulation rate in the prior art, and achieve more High bioavailability and better sustained release effect.
Patent Information
- Application Number
- CN202411599495.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-11
AI Technical Summary
In the prior art, oral nidanib has low bioavailability, and the encapsulation rate of inhalable nidanib is low and the sustained release effect is poor, making it difficult to effectively target the transport to the lungs and prolong retention in the lungs. time.
Nanoparticles are prepared by ionic cross-linking method, and self-assembled through electrostatic interaction between cationic polysaccharides and anionic polymers to form polymer nanocarriers and load nidanib, thereby improving the encapsulation rate and sustained release effect of the drug.
It improves the bioavailability and efficacy of nidanib, extends the retention time of the drug in the lungs, enhances the local drug concentration in the lungs, and achieves better therapeutic effects.
Smart Images

Figure CN119454666A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of pharmaceutical preparations, and in particular to an inhalable drug-loaded nanoparticle and a preparation method and application thereof. Background Art
[0002] Pulmonary fibrosis is a stubborn, chronic, progressive lung disease characterized by the gradual replacement of lung tissue with fibrosis, which leads to a continuous decline in respiratory function, shortness of breath, and a sharp decline in quality of life. Idiopathic pulmonary fibrosis (IPF) is the most common subtype, with a median survival of only a short 3-5 years. At present, the academic community has not found a way to completely cure IPF, and can only use some treatment options to control symptoms and slow the progression of the disease, including but not limited to oxygen therapy, lung transplantation, and various drug treatments. In recent years, significant progress has been made in the field of drug treatment of IPF, but there are still many challenges to be overcome, including how to diagnose earlier, improve patient treatment compliance, and improve patient prognosis. Therefore, it is crucial to study new drug formulations to solve these existing problems.
[0003] Nintedanib (NDNB) is a tyrosine kinase inhibitor that is regulated by the U.S. Food and Drug Administration. The US Food and Drug Administration (FDA) has approved it for marketing for the treatment of idiopathic pulmonary fibrosis (IPF). Conventional oral administration of nintedanib can easily lead to liver damage in patients, and may also cause adverse gastrointestinal reactions such as diarrhea and nausea. Therefore, it is necessary to target nintedanib to the lungs as much as possible. In addition, the current oral dosage forms have the problem of low bioavailability, while inhaled preparations can directly enter the lungs, thereby more effectively treating lung diseases such as idiopathic pulmonary fibrosis. For example, the modified ethanol injection method described in the article "Preparation and Characterization Study of Nintedanib Nanoliposomes" in the Journal of Army Medical University, Issue 46(14) in 2024 can prepare targeted nintedanib liposomes with an encapsulation rate of about 32%. Another example is a kind of inhalable lipid nanoparticles and its preparation method and application disclosed in patent CN202310267601.8. This technical scheme encapsulates the anti-fibrosis drug nintedanib and the first-line anti-diabetic drug metformin in inhalable liposomes for the treatment of bleomycin-induced pulmonary fibrosis. This technical scheme uses dipalmitoylphosphatidylcholine, cholesterol and distearoylphosphatidylacetamide-polyethylene glycol to prepare nintedanib liposomes with a hydrated particle size of about 100 nm.
[0004] In order to achieve targeted transport of nintedanib in the prior art, the emulsion volatilization method is often used to prepare lipid carriers, which introduces a large amount of organic solvents during the preparation process and has poor biosafety. In addition, the encapsulation rate of nintedanib drug-loaded particles in the prior art is low, resulting in rapid release of the drug after entering the body, resulting in a shortened half-life of the drug in the body and requiring more frequent administration. Summary of the invention
[0005] The present invention aims to overcome the defects in the prior art that oral nintedanib has low bioavailability, but the existing inhalable nintedanib has low encapsulation rate and poor sustained-release effect. The present invention attempts to use an ion crosslinking method to prepare nanoparticles, prolong the retention time of nintedanib in the lungs, increase the local drug concentration in the lungs, and improve the drug bioavailability. An inhalable drug-loaded nanoparticle and its preparation method and application are proposed to overcome the above defects.
[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions: In a first aspect, the present invention discloses an inhalable drug-loaded nanoparticle: It includes a polymer nanocarrier, and nintedanib loaded on the polymer nanocarrier through hydrogen bonds; The polymer nanocarrier is self-assembled by cationic polysaccharide and anionic polymer through electrostatic interaction; Nintedanib has a good effect in treating pulmonary fibrosis, but the solubility of Nintedanib is low, and the current oral dosage forms all have the problem of low bioavailability, while the inhalation preparation can directly enter the lungs, thereby more effectively treating lung diseases. Therefore, the present invention prepares Nintedanib into nanoparticles, and the particle size meets the inhalation standard, thereby achieving the effect of improving bioavailability and improving efficacy.
[0007] The molecular structure of nintedanib contains multiple polar groups, such as hydroxyl and amino groups. Cationic polysaccharides are high molecular weight substances containing amino groups or amino functional groups in their structures. Cationic polysaccharides and anionic polymers form polymer nanocarriers with stable internal structures through electrostatic interactions. The polymer nanocarriers contain multiple receptors for forming hydrogen bonds. Free nintedanib can form multiple hydrogen bonds with the polymer nanocarriers through the polar groups on them, achieving a stable binding effect, thereby increasing the drug loading and encapsulation rate. In this way, not only can more nintedanib be targeted and transported to the lungs, but the nintedanib encapsulated therein can also be slowly released to achieve a sustained release effect.
[0008] Furthermore, the cationic polysaccharide is chitosan. Chitosan is the only polysaccharide in nature that carries a positive charge. Chitosan has good biocompatibility, blood compatibility, self-degradation and metabolism, non-toxicity and high safety. More importantly, chitosan has excellent mucosal adhesion. The design and preparation of chitosan-based pulmonary inhalation nanoformulations can prolong the retention time of nintedanib in the lungs, enhance its distribution in the lungs, and increase the local drug concentration in the lungs.
[0009] Furthermore, the anionic polymer contains carboxyl groups. The hydroxyl groups in nintedanib and the amino groups on the cationic polysaccharide can form hydrogen bonds with the carboxyl groups in the anionic polymer, and the synergistic effect of multiple hydrogen bonds can significantly enhance the binding force between molecules.
[0010] Further, the anionic polymer is one or more of polyaspartic acid, polyacrylic acid, and polyglutamic acid. The above-mentioned anionic polymers all contain carboxyl groups, and together with the amino groups in the cationic polysaccharide, they form multiple hydrogen bonds with multiple polar groups in nintedanib, significantly enhancing the binding force between molecules, greatly improving the drug loading efficiency and achieving a sustained release effect. The polyaspartic acid therein is an amino acid polymer that naturally exists in snail and mollusk shells and has good biocompatibility and biodegradability. The polyglutamic acid therein is an anionic natural polymer with an active carboxyl group, which is easily soluble in water, non-toxic, biocompatible and degradable, and can be biodegraded into endogenous substances glutamic acid in nature or in the human body, and is not easy to produce accumulation and toxic side effects.
[0011] Furthermore, the particle size of the inhalable drug-loaded nanoparticles is between 220 and 235 nm. Ideal inhaled nanoparticles should be able to be effectively deposited in the alveolar region so that the drug can be absorbed by the capillaries in the alveoli and enter the blood circulation. When the particle size of the nanoparticles is too large, the drug is more likely to be deposited in the upper respiratory tract and cannot effectively reach the alveoli; when the particle size of the nanoparticles is too small, the drug is more likely to be discharged from the lungs with the respiratory airflow, and a good therapeutic effect cannot be achieved. Therefore, the present invention controls the particle size of the inhalable nintedanib to between 220 and 235 nm, ensuring that the drug can reach the alveoli while not being easily discharged from the lungs with breathing.
[0012] Furthermore, the encapsulation rate of the inhalable drug-loaded nanoparticles is ≥45%. To ensure the drug effect, a higher encapsulation rate means that more drugs are delivered to the target location and the encapsulated drugs can be slowly released.
[0013] Furthermore, the mass ratio of the cationic polysaccharide to the anionic polymer is 1:0.2-0.6.
[0014] Furthermore, the mass ratio of nintedanib to cationic polysaccharide is 0.4-0.7:1.
[0015] In a second aspect, the present invention discloses a method for preparing inhalable drug-loaded nanoparticles, comprising the following steps: S1, dissolving the cationic polysaccharide in an acetic acid solution, and then dissolving nintedanib in the cationic polysaccharide acetic acid solution; S2. Under stirring conditions, slowly dripping the anionic polymer solution into the cationic polysaccharide acetic acid solution; S3, centrifuging and concentrating to obtain the inhalable drug-loaded nanoparticles.
[0016] In a third aspect, the present invention discloses a use of the above-mentioned inhalable drug-loaded nanoparticles in the preparation of a drug for treating idiopathic pulmonary fibrosis.
[0017] Therefore, the present invention has the following beneficial effects: (1) The present invention constructs a nano drug delivery system by using cationic polysaccharides and anionic polymers, which can achieve a higher encapsulation rate, have a longer lung retention time, and increase the local blood drug concentration in the lungs to achieve a better therapeutic effect.
[0018] (2) The present invention prepares nanoparticles by an ionic crosslinking method, which reduces the introduction of organic solvents, and through the cationic polysaccharides and anionic polymers selected in the preferred scheme, the drug-loaded nanoparticles have good biocompatibility, biodegradability, etc.
[0019] (3) The inhalable drug-loaded nanoparticles prepared by the present invention have a smooth spherical surface and good dispersibility, which can significantly improve the drug loading efficiency and achieve a sustained release effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the SEM image of NDNB / CS-PGA NPs prepared in Example 1 of the present invention.
[0021] Figure 2 This is the particle size distribution diagram of NDNB / CS-PGA NPs prepared in Example 1 of the present invention.
[0022] Figure 3 This is the potential distribution diagram of NDNB / CS-PGA NPs prepared in Example 1 of the present invention.
[0023] Figure 4 The release curves of NDNB / CS-PGA NPs and NDNB API in PBS and the comparison of cumulative release rates are shown.
[0024] Figure 5 This is a comparison of the half-inhibitory rates of different concentrations of NDNB / CS-PGA NPs and NDNB on Calu-3 cells.
[0025] Figure 6 This is a comparison of the half inhibition rates of different concentrations of NDNB / CS-PGA NPs and NDNB on HFL1 cells. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is further clearly and completely described below through specific examples and in combination with the accompanying drawings. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given, but they are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The experimental methods used in the following embodiments are conventional methods unless otherwise specified, and the materials, reagents, etc. used in the embodiments, unless otherwise specified, can be obtained from commercial channels.
[0027] The particle size and polydispersity index (PDI) of the drug-loaded nanoparticles prepared in the following examples and comparative examples were measured by a laser particle size analyzer, and the concentration of nintedanib in the nintedanib nanoparticles was calculated by a UV spectrophotometer using the nintedanib-methanol standard curve, and the encapsulation efficiency (EE) and drug loading (DL) of the nanoparticles were obtained according to the formula.
[0028] Example 1 Dissolve 1 part of chitosan in an aqueous solution containing 0.1% acetic acid, and then weigh 0.5 parts of nintedanib and dissolve it in the above solution; 0.4 parts of polyglutamic acid was dissolved in pure water, and the stirring rate was set to 800 rpm for 5 min. During the stirring process, the polyglutamic acid solution was slowly dripped into the acetic acid solution of chitosan and nintedanib to obtain a nanoparticle suspension; After stirring, the nanoparticle suspension was transferred to an ultrafiltration centrifuge tube (4000 D), centrifuged at 2000 rpm for 20 min, concentrated to remove unencapsulated free nintedanib, and then stored in a refrigerator at 4°C away from light for later use.
[0029] Example 2 Dissolve 1 part of chitosan in an aqueous solution containing 0.1% acetic acid, and then weigh 0.5 parts of nintedanib and dissolve it in the above solution; 0.2 parts of polyglutamic acid was dissolved in pure water, and the stirring rate was set to 800 rpm for 5 min. During the stirring process, the polyglutamic acid solution was slowly dripped into the acetic acid solution of chitosan and nintedanib to obtain a nanoparticle suspension; After stirring, the nanoparticle suspension was transferred to an ultrafiltration centrifuge tube (4000 D), centrifuged at 2000 rpm for 20 min, concentrated to remove unencapsulated free nintedanib, and then stored in a refrigerator at 4°C away from light for later use.
[0030] Example 3 Dissolve 1 part of chitosan in an aqueous solution containing 0.1% acetic acid, and then weigh 0.5 parts of nintedanib and dissolve it in the above solution; 0.6 parts of polyglutamic acid was dissolved in pure water, and the stirring rate was set to 800 rpm for 5 min. During the stirring process, the polyglutamic acid solution was slowly dripped into the acetic acid solution of chitosan and nintedanib to obtain a nanoparticle suspension; After stirring, the nanoparticle suspension was transferred to an ultrafiltration centrifuge tube (4000 D), centrifuged at 2000 rpm for 20 min, concentrated to remove unencapsulated free nintedanib, and then stored in a refrigerator at 4°C away from light for later use.
[0031] Example 4 Dissolve 1 part of chitosan in an aqueous solution containing 0.1% acetic acid, and then weigh 0.4 parts of nintedanib and dissolve it in the above solution; 0.4 parts of polyglutamic acid was dissolved in pure water, and the stirring rate was set to 800 rpm for 5 min. During the stirring process, the polyglutamic acid solution was slowly dripped into the acetic acid solution of chitosan and nintedanib to obtain a nanoparticle suspension; After stirring, the nanoparticle suspension was transferred to an ultrafiltration centrifuge tube (4000 D), centrifuged at 2000 rpm for 20 min, concentrated to remove unencapsulated free nintedanib, and then stored in a refrigerator at 4°C away from light for later use.
[0032] Example 5 Dissolve 1 part of chitosan in an aqueous solution containing 0.1% acetic acid, and then weigh 0.7 parts of nintedanib and dissolve it in the above solution; 0.4 parts of polyglutamic acid was dissolved in pure water, and the stirring rate was set to 800 rpm for 5 min. During the stirring process, the polyglutamic acid solution was slowly dripped into the acetic acid solution of chitosan and nintedanib to obtain a nanoparticle suspension; After stirring, the nanoparticle suspension was transferred to an ultrafiltration centrifuge tube (4000 D), centrifuged at 2000 rpm for 20 min, concentrated to remove unencapsulated free nintedanib, and then stored in a refrigerator at 4°C away from light for later use.
[0033] Comparative Example 1 Dissolve 1 part of chitosan in an aqueous solution containing 0.1% acetic acid, and then weigh 0.5 parts of nintedanib and dissolve it in the above solution; 0.1 parts of polyglutamic acid was dissolved in pure water, and the stirring rate was set to 800 rpm for 5 min. During the stirring process, the polyglutamic acid solution was slowly dripped into the acetic acid solution of chitosan and nintedanib to obtain a nanoparticle suspension; After stirring, the nanoparticle suspension was transferred to an ultrafiltration centrifuge tube (4000 D), centrifuged at 2000 rpm for 20 min, concentrated to remove unencapsulated free nintedanib, and then stored in a refrigerator at 4°C away from light for later use.
[0034] Comparative Example 2 Dissolve 1 part of chitosan in an aqueous solution containing 0.1% acetic acid, and then weigh 0.5 parts of nintedanib and dissolve it in the above solution; 0.8 parts of polyglutamic acid was dissolved in pure water, and the stirring rate was set to 800 rpm for 5 min. During the stirring process, the polyglutamic acid solution was slowly dripped into the acetic acid solution of chitosan and nintedanib to obtain a nanoparticle suspension; After stirring, the nanoparticle suspension was transferred to an ultrafiltration centrifuge tube (4000 D), centrifuged at 2000 rpm for 20 min, concentrated to remove unencapsulated free nintedanib, and then stored in a refrigerator at 4°C away from light for later use.
[0035] Comparative Example 3 Dissolve 1 part of chitosan in an aqueous solution containing 0.1% acetic acid, and then weigh 0.3 parts of nintedanib and dissolve it in the above solution; 0.4 parts of polyglutamic acid was dissolved in pure water, and the stirring rate was set to 800 rpm for 5 min. During the stirring process, the polyglutamic acid solution was slowly dripped into the acetic acid solution of chitosan and nintedanib to obtain a nanoparticle suspension; After stirring, the nanoparticle suspension was transferred to an ultrafiltration centrifuge tube (4000 D), centrifuged at 2000 rpm for 20 min, concentrated to remove unencapsulated free nintedanib, and then stored in a refrigerator at 4°C away from light for later use.
[0036] Comparative Example 4 Dissolve 1 part of chitosan in an aqueous solution containing 0.1% acetic acid, and then weigh 0.8 parts of nintedanib and dissolve it in the above solution; 0.4 parts of polyglutamic acid was dissolved in pure water, and the stirring rate was set to 800 rpm for 5 min. During the stirring process, the polyglutamic acid solution was slowly dripped into the acetic acid solution of chitosan and nintedanib to obtain a nanoparticle suspension; After stirring, the nanoparticle suspension was transferred to an ultrafiltration centrifuge tube (4000 D), centrifuged at 2000 rpm for 20 min, concentrated to remove unencapsulated free nintedanib, and then stored in a refrigerator at 4°C away from light for later use.
[0037] Comparative Example 5 The reverse evaporation method was used to take 10 mg of DPPC, 1 mg of DPPG, 1 mg of DPPE-PEG2000 and 1.5 mg of cholesterol into a 50 mL eggplant-shaped bottle. After adding 2 mL of anhydrous ethanol to dissolve, 0.7 mL of 0.6 mg / mL nintedanib solution was added. The eggplant-shaped bottle was placed in an ultrasonic cleaner (200 W) and ultrasonicated in a water bath for 30 min to form a W / O oil-water mixture. After removing the anhydrous ethanol by rotary evaporation under reduced pressure (60 min), pure water was added for hydration for 30 min. The hydrated solution was filtered three times through a 200 nm filter and filtered using a filter with a relative molecular mass of 10×10 3 The free drug is removed by dialyzing in a dialysis bag to obtain nintedanib liposomes.
[0038] Comparative Example 6 Using the ethanol injection method, 10 mg of DPPC, 1 mg of DPPG, 1 mg of DPPE-PEG2000, and 1.5 mg of cholesterol were taken into a 20 mL sample bottle, and 1 mL of anhydrous ethanol was added to dissolve them. The sample bottle was placed in an ultrasonic cleaner (200 W) and ultrasonicated at a constant temperature (20 °C) for 20 min. 3 mL of 0.6 mg / mL nintedanib solution was quickly injected into the sample bottle with a 5 mL syringe, and ultrasonication was performed while injecting. After ultrasonication for 20 min, a 10×10 3 The dialysis bag is dialyzed to remove free drugs and anhydrous ethanol to obtain nintedanib liposomes.
[0039] Table 1 Performance of drug-loaded nanoparticles in different groups The particle size, PDI, encapsulation efficiency and drug loading of the nanoparticles prepared by different groups are shown in Table 1. The nanoparticles prepared in Examples 1-5 have uniform particle size, good dispersibility, and an encapsulation efficiency of up to 70%, and have a higher drug loading under the premise of a high encapsulation efficiency. Compared with Comparative Example 1, when too little anionic polymer is added, the formation of the polymer carrier is hindered, resulting in a significant reduction in the encapsulated nintedanib, and both the encapsulation efficiency and the drug loading are very low. Compared with Comparative Example 2, when too much anionic polymer is added, the particle size of the drug-loaded nanoparticles is reduced, and both the encapsulation efficiency and the drug loading are reduced. Compared with Comparative Example 3, the amount of nintedanib added is too little, although there is a higher encapsulation efficiency, the drug loading does not meet the requirements. Compared with Comparative Example 4, when too much nintedanib is added, the drug loading increases, but the lower encapsulation efficiency is difficult to ensure the sustained release effect of the drug, and the drug particle size of the comparative example is relatively small, and it is easy to be discharged from the lungs with breathing. Compared with Comparative Examples 5 and 6, the nintedanib liposomes prepared by the reverse evaporation method and the ethanol injection method have a large gap with the examples in terms of both encapsulation efficiency and drug loading.
[0040] In order to verify the stability of the drug-loaded nanoparticles of the present invention, a stability experiment was conducted using chitosan and polyglutamic acid inhalable drug-loaded nanoparticles (NDNB / CS-PGA NPs) as an example: The NDNB / CS-PGA NPs were stored in a 4°C refrigerator, and the particle size was detected on the 1st, 5th, 10th and 15th days. It was observed that there was no obvious change in its appearance. The particle size of the nanoparticles slowly increased over time. It may be that the outer layer of the nanoparticles contacted with water molecules to form a hydration layer. The particle size of the drug-loaded nanoparticles did not change much within 15 days. It can be seen from Table 5 that NDNB / CS-PGA NPs have good stability.
[0041] Table 2 Particle size changes of NDNB / CS-PGA NPs over time To verify the sustained-release effect of the drug-loaded nanoparticles of the present invention, a sustained-release experiment was performed: At pH 7.4, the cumulative release of NDNB / methanol and NDNB / CS-PGA NPs in buffer was recorded. Figure 4 It can be seen that when the drug is encapsulated by the nanocarrier, the release curve is completely different from the raw material. As shown in the figure, the release of the NDNB-NPs drug-loaded nanoparticle solution is shown. Within 0-8 hours, NDNB-NPs are released rapidly, with a cumulative release of 66.03%. Within 8-48 hours, the release curve gradually stabilizes, and after 48 hours, the cumulative release reaches a maximum of 79.67%. Compared with the NDNB / methanol solution, the overall release time of NDNB-NPs is longer and the cumulative release is higher, indicating that the drug encapsulated in the chitosan nanoparticles can be released slowly, play a sustained release role, and allow nintedanib to be more fully dispersed in water.
[0042] In order to verify the biocompatibility of the drug-loaded nanoparticles of the present invention, a cytotoxicity experiment was performed: The cytotoxicity of NDNB / CS-PGA NPs and NDNB was evaluated by calculating the half inhibition rate on Calu-3 cells. Figure 5 It can be seen that at the same drug concentration, the nanoparticle-encapsulated NDNB / CS-PGA NPs have a smaller inhibition on Calu-3 cells, with a half inhibition rate of 48.75 μg / mL, while the half inhibition rate of NDNB / CS-PGA NPs on Calu-3 cells is 35.00 μg / mL. As the drug concentration increases, the difference in cell viability between NDNB / CS-PGA NPs and NDNB becomes greater. Therefore, at the same concentration, NDNB / CS-PGANPs show lower cytotoxicity than NDNB.
[0043] In order to verify the effect of the drug-loaded nanoparticles of the present invention in preparing drugs for treating idiopathic pulmonary fibrosis, an anti-fibrotic activity experiment was conducted: The antifibrotic activity of NDNB / CS-PGA NPs and NDNB was evaluated by calculating the half inhibition rate on HFL1 cells (human embryonic lung fibroblasts). Figure 6 It was observed that at the same drug concentration, nanoparticle-encapsulated NDNB / CS-PGA NPs had a stronger inhibitory effect on HFL1 cells, with a half inhibition rate of 12.53 μg / mL, which was higher than the half inhibition rate of NDNB on HFL1 cells of 17.84 μg / mL. This may be because after being encapsulated by chitosan, nintedanib can be better released and show better anti-fibrosis activity.
[0044] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.
Claims
1. An inhalable drug-loaded nanoparticle, characterized in that: It includes a polymer nanocarrier, and nintedanib loaded on the polymer nanocarrier through hydrogen bonds; The polymer nanocarrier is self-assembled by cationic polysaccharide and anionic polymer through electrostatic interaction.
2. The inhalable drug-loaded nanoparticles according to claim 1, characterized in that: The cationic polysaccharide is chitosan.
3. The inhalable drug-loaded nanoparticles according to claim 2, characterized in that: The anionic polymer contains a carboxyl group.
4. The inhalable drug-loaded nanoparticles according to claim 3, characterized in that: The anionic polymer is one or more of polyaspartic acid, polyacrylic acid and polyglutamic acid.
5. The inhalable drug-loaded nanoparticles according to any one of claims 1 to 4, characterized in that: The particle size of the inhalable drug-loaded nanoparticles is between 220 and 235 nm.
6. The inhalable drug-loaded nanoparticles according to any one of claims 1 to 4, characterized in that: The encapsulation rate of the inhalable drug-loaded nanoparticles is ≥45%.
7. The inhalable drug-loaded nanoparticles according to any one of claims 1 to 4, characterized in that: The mass ratio of the cationic polysaccharide to the anionic polymer is 1:0.2-0.
6.
8. The inhalable drug-loaded nanoparticles according to any one of claims 1 to 4, characterized in that: The mass ratio of nintedanib to cationic polysaccharide is 0.4-0.7:
1.
9. A method for preparing inhalable drug-loaded nanoparticles according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, dissolving the cationic polysaccharide in an acetic acid solution, and then dissolving nintedanib in the cationic polysaccharide acetic acid solution; S2. Under stirring conditions, slowly dripping the anionic polymer solution into the cationic polysaccharide acetic acid solution; S3, centrifuging and concentrating to obtain the inhalable drug-loaded nanoparticles.
10. Use of the inhalable drug-loaded nanoparticles according to any one of claims 1 to 8 in the preparation of a drug for treating idiopathic pulmonary fibrosis.
Citation Information
Patent Citations
Inhalable lipid nanoparticles as well as preparation method and application thereof
CN116492317A
Nanoparticles for paracellular drug delivery
US20060073210A1
Nanosuspension formulation for treatment of pulmonary fibrosis
US20240285545A1
Pharmaceutical composition of nanoparticles
US8007768B1
Pharmaceutical composition of nanoparticles
US8192718B1
Cited By
Nintedanib inhalation dry powder as well as preparation method and application thereof
CN120837461A